On nonisothermal elastoplastic analysis of shell components employing realistic hardening responses - TONKOVIC, Zdenko; SORIC, Jurica; KRÄTZIG, Wilfried B (International journal of solids and structures, 2001)
In the present paper, efficient numerical algorithms for elastoplastic analysis of shell-like structural components will be proposed employing nonisothermal, realistic, highly nonlinear hardening responses. The closest point projection integration algorithm is presented using a Reissner–Mindlin type kinematic shell model, completely formulated in tensor notation. Further, a consistent elastoplastic tangent modulus is derived, which ensures high convergence rates in the global iteration approach. The integration algorithm has been implemented into a layered assumed strain isoparametric finite element, which also enables geometrical nonlinearities including finite rotations. The nonisothermal elastoplastic response of a circular cylindrical shell and a box column under axial compression is analysed. Under the assumption of an adiabatic process, the increase in temperature is computed during elastoplastic deformation. Robustness and numerical stability of the proposed algorithms are demonstrated.